2010
DOI: 10.1007/s00467-010-1560-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase as a predictor of kidney involvement in patients with sickle cell anemia

Abstract: A retrospective chart review of 40 patients with sickle cell anemia (SCA) between the ages of 5-19 years who were seen within a 1-year period was performed to determine clinical and laboratory correlates for microalbuminuria and proteinuria. Age, sex, height, body mass index (BMI), serum creatinine [and estimated glomerular filtration rate (eGFR) by Schwartz and MDRD formulas], type of SCA, hemoglobin (Hb) level [total Hb and hemoglobin F percentage (HbF%)], lactate dehydrogenase (LDH) level, reticulocyte coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 28 publications
7
38
1
Order By: Relevance
“…Literature on this issue is divergent where some studies have found a relationship [45,46] and others have not [47,48]. Further studies are needed to continue understanding the pathophysiological mechanisms underlying renal dysfunction in SCD.…”
Section: Discussionmentioning
confidence: 92%
“…Literature on this issue is divergent where some studies have found a relationship [45,46] and others have not [47,48]. Further studies are needed to continue understanding the pathophysiological mechanisms underlying renal dysfunction in SCD.…”
Section: Discussionmentioning
confidence: 92%
“…In children with SCA, significant associations have been found between proteinuria and the hemolysis markers of low hemoglobin (Hb) and high lactate dehydrogenase (LDH). 5,13 Similar studies in adults, however, have not replicated this finding, although an association between low hemoglobin levels and hyperfiltration have been reported. [14][15] More recently, Maier-Redelsperger et al utilized a marker of red cell survival derived from mature red blood cell hemoglobin (RBC Hb) and reticulocyte hemoglobin (RET Hb), and showed that the log (RBC Hb/RET Hb) was highly correlated with LDH, bilirubin and albuminuria.…”
Section: Introductionmentioning
confidence: 92%
“…Univariate and multivariate analyses showed a significant correlation between LDH level and microalbuminuria and proteinuria. 7 Kato et al reported an association between hemolysis and clinical subphenotypes of SCD, including pulmonary hypertension (PH), but the diagnosis of hemolysis was based on LDH levels. 8 Conversely, Ataga et al reported a significant correlation between PH and microalbuminuria, but no correlation with parameters of hemolysis.…”
Section: To the Editormentioning
confidence: 99%